An overview of Shari'ah compliant healthcare services in Malaysia - Zawawi, Majdah; Othman, Khadijah (The Malaysian Consumer and Family Economics Association, 2017)
Shari'ah compliant healthcare services is designed to provide Muslim patients with medical treatment that abides by Islamic principles which also includes halal medicine. There are several issues that arise when discussing this type of healthcare services. For example, Muslim patients face significant challenges in recieving treatment in conventional hospitals, which includes privacy issues during treatment, cross-gender interactions between patients and medical practitioners as well as the status of the pharmaceuticals provided.